Engagement During Storybook Reading Promotes Indonesian Children’s English Vocabulary Acquisition - Rizka Junhita Rahma Wanodya; Nur Arifah Drajati; Sri Samiati Tarjana (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
The purpose of this study is to explore the engagement of parents-child during the implementation of storybook reading to promote Indonesian children’s English vocabulary acquisition. The researcher uses questionnaire and interview to collect the data. There are 81 respondents who fulfil the questionnaire. The researcher applies an in-depth open ended interview. The result shows that children acquire new English vocabularies through the implementation of storybook reading by parents from home-based activity. The researcher uses Narrative Inquiry as the research methodology. The implication of this study to increase the parents’ awareness on the benefit of implementing storybook reading to promote children’s English vocabulary acquisition. The other implication is guiding parents to create engagement to reach the goals.